Structural diversity of mixed polypnictogen complexes: dicationic E2E′2 (E ≠ E′ = P, As, Sb, Bi) chains, cycles and cages stabilized by transition metals. Issue 43 (22nd October 2021) - Dütsch, Luis; Riesinger, Christoph; Balázs, Gábor; Seidl, Michael; Scheer, Manfred
Abstract : Unique dicationic hetero-tetrapnictogen E2 E′2 (E ≠ E′ = P, As, Sb, Bi) chains and cages are obtained via oxidation of the tetrahedranes [{CpMo(CO)2 }2 (μ, η 2 :η 2 -EE′)]. Exchange of the counterion causes an unusual cyclization of the As2 Sb2 ligand. Abstract : The reactivity of the tetrahedral dipnictogen complexes [{CpMo(CO)2 }2 (μ, η 2 :η 2 -EE′)] (E, E′ = P, As, Sb, Bi; "Mo2 EE′ ") towards different one-electron oxidation agents is reported. Oxidation with [Thia][TEF] (Thia + = C12 H8 S2 + ; TEF − = Al{OC(CF3 )3 }4 − ) leads to the selective formation of the radical monocations [Mo2 EE′]˙ +, which immediately dimerize to the unprecedented dicationic E2 E′2 ligand complexes [{CpMo(CO)2 }4 (μ4, η 2 :η 2 :η 2 :η 2 -E′EEE′)] 2+ via E–E bond formation. Single crystal X-ray diffraction revealed that, in the case of Mo2 PAs and Mo2 PSb, P–P bond formation occurs yielding zigzag E2 P2 (E = As (1 ), Sb (2 )) chains, whereas Mo2 SbBi forms a Sb2 Bi2 (5 ) cage, Mo2 AsSb an unprecedented As2 Sb2 unit representing an intermediate stage between a chain- and a cage-type structure, and Mo2 AsBi a novel planar As2 Bi2 (4a ) cycle. Therefore, 1–5 bear the first substituent-free, dicationic hetero-E4 ligands, stabilized by transition metal fragments. Furthermore, in the case of Mo2 AsSb, the exchange of the counterion causes changes in the molecular structure yielding an unusual, cyclic As2 Sb2 ligand. The experimental results are corroborated by DFT calculations.